Effects of Ralgro and DES implants during the suckling period on later reproductive performance of beef heifers - Sprott, L.R.; Corah, L.R.; Kiracofe, G.H.; McKee, M.; Schwartz, F.L. (Kansas State University. Agricultural Experiment Station, 2011)
Heifers were given either one or two Ralgro implants or one DES implants during the suckling period with no obvious effect on later reproductive performance when the heifers were bred as yearlings. However, conception rates in control heifers were low in two trials, so more studies are needed for conclusive results.
Keywords: Beef; Implants; Reproductive performance; Heifers